Sistem Pembuktian Terbalik dalam Pemberantasan Tindak Pidana Korupsi - Made Mahadwiva Surya Krishna; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Jurnal Interpretasi Hukum, 2021)
Corruption is a special crime that is extraordinary in nature (extra ordinary crime), as a result the resolution is also extraordinary by using the principle of retroactivity with an accelerated settlement process using evidence as regulated in Article 26A of Law No. 31 of 1999 No.UU No. 20 of 2001. The purpose of the research is to analyze and reveal the arrangement of evidence in criminal corruption and the strength of the reversal proof system in corruption. The research method is normative law with a statutory approach and a conceptual approach. The sources of legal materials are primary and secondary. From the legal materials that have been collected then analyzed using the construction technique of interpretation, argumentation, evaluation and systematization. The research results reveal that the arrangement of evidence is compiled in criminal corruption, namely evidence in the form of witness evidence, letters, instructions and statements from experts and defendants, other evidence in the form of electronic or electronic information based on Article 26A of Law No. 31 of 1999 No. UU no. 20 of 200 1. The proof system in criminal corruption adopts a limited reversal proof system, which is no longer the prosecutor's obligation to decide, but the suspect must prove that his assets are not the result of a crime.